The rule of law and the elimination of racial discrimination - Jiménez-Sánchez, Carolina (My University, 2019)
This paper analyses the reception of “minority” rights in the UN Human Rights protection system, checking the concept of the “rule of law” included in the UN Charter and in International Law, giving particular attention to the procedures of the Committee on the Elimination of Racial Discrimination (CERD).
Keywords: Derechos humanos; Discriminación racial; Rule of law; Racial discrimination; Human rights